Cutis Tuberculosis - Ilhami Rusdi, Yudika; Hijriani Hardianti, Rahmi; Wahyu Alfian, Lalu; Nabila, Cahya; Nurul Milenia, Uni (Jurnal KESANS : Kesehatan dan Sains, 2021)
Background: Tuberculosis (TB) is spreading globally, and more than two billion people (about 30% of the world's population) are thought to be infected with M. tuberculosis. Tuberculosis cutis is an extrapulmonary Mycoterium tuberculosis infection that attacks the skin. Research Methods: The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were conducted on the online portals of journal publications such as MedScape, Google Scholar and NCBI (ncbi.nlm.nih.gov). Results: Cutaneous TB can be transmitted through exposure to the lungs or infected aerosols entering the lungs. Cutaneous TB is divided into True Cutaneous TB which consists of primary and secondary TB, and Tuberculid Overall, the treatment of cutaneous TB is similar to that of systemic TB, which tends towards multi-drug therapy. Several anti-tuberculosis drugs such as isoniazid, rifampin, and pyrazinamide have been recommended as drugs for the treatment of cutaneous tuberculosis. It was reported that in a five-year follow-up approximately 12.5% ??of cutaneous TB patients showed relapse after standard anti-TB therapy. Conclusion: To reduce the mortality rate, the public needs to be given education regarding the dangers and ways to prevent TB disease to increase public awareness. More long-term studies are needed to understand the recurrence rate of various cutaneous tuberculosis under current treatment recommendations, especially in immunocompromised patients.